1982
DOI: 10.1161/01.cir.65.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combined valvular prolapse syndrome by two-dimensional echocardiography.

Abstract: SUMMARY The patterns of aortic and tricuspid valve motion in 50 patients with mitral valve prolapse were analyzed by wide-angle, phased-array, two-dimensional echocardiography. Twelve patients (24%) had redundant aortic leaflets bulging into the left ventricular outflow tract during diastole. Eight of 12 patients had aortic regurgitation and seven of 12 had M-mode echocardiographic evidence of aortic valve prolapse. One patient underwent mitral and aortic valve replacement, and the excised valves revealed mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…This is in agreement with the observations of Ogawa et al 9 Forty-one patients (50%) were found to have isolated MVP. Their mean age was 45 years (range 15-80 years).…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with the observations of Ogawa et al 9 Forty-one patients (50%) were found to have isolated MVP. Their mean age was 45 years (range 15-80 years).…”
Section: Resultssupporting
confidence: 93%
“…'7 48 Thus cross sectional echocardiography showed concomitant tricuspid prolapse in 48% of 64 patients with mitral valve prolapse'7 and in 190/o of 31 patients with mitral valve prolapse.48 Contrast echocardiography is helpful in evaluating tricuspid regurgitation in this situation. '7 47 The general observation has been made that among subjects with tricuspid valve prolapse a more severe form of mitral valve prolapse is prevalent. '7 Although it has been claimed that tricuspid valve prolapse occurs rarely as an isolated lesion,3 careful cross sectional echocardiographic technique has been shown to be capable of demonstrating it in 6% of an assortc: group of 112 subjects without mitral valve prolapse,48 and it can be shown angiographically when prolapse is not evident on the contralateral ventricular cineangiogram.44 Data are lacking on the histological state of prolapsing tricuspid valves where there has not been concomitant mitral valve prolapse but the prolapse may be secondary to disturbed right ventricular dynamics.…”
Section: Malcolmmentioning
confidence: 99%
“…Tricuspid valve prolapse has been found in 19.7-48% of patients with mitral valve prolapse [1][2][3] and less commonly in pa tients with rheumatic heart disease, pulmo nary hypertension with right heart failure, or other cardiac conditions [1,4], Tricuspid valve prolapse unassociated with other car diac abnormalities, however, has only rarely been reported. Werner et al [4] assessed the tricuspid valve in 500 consecutive patients without mitral valve prolapse or congenital heart disease, and no patients were found with an échocardiographie pattern of tricus pid prolapse.…”
Section: Introductionmentioning
confidence: 99%